TEACHER'S STRATEGIES IN GETTING STUDENTS' ATTENTIONS DURING TRANSITION - Fauzia, Wulan (2012)
This study, entitled Teacher's Strategies in Getting Students' Attention, investigated the teacher's strategies in getting students' attention during transition. The purposes of the study were to find out strategies used by the teacher and the students' responses to the strategies. During transition between activities in classroom, behavioral problems were likely to arise and potentially consumed instructional times and teacher's energy. Since students could not proceed classroom activities without paying attention to the teacher's instruction, various strategies in getting the students' attention are necessary. This study employed qualitative research design and case study methodology. The data were collected through five observations and two interviews. The participants of this study were an English teacher and a class of third grade students in a state elementary school in Bandung. The findings revealed that the teacher used desisting, chant, sound, clapping and singing a song in getting students' attention. The students responded the strategies in two ways, positive way which means that the students paid attention to the teacher and negative one which means none or only some students paid attention to the teacher. Finally, it can be concluded that teachers might develop various kinds of strategies in getting students attention but it is also recommended that teachers need to consider supporting factors to the strategies such as students' and classroom's characteristics. Penelitian yang berjudul entitled Teacher's Strategies in Getting Students' Attention ini, meneliti tentang strategi guru dalam menarik kembali perhatian siswa ketika masa transisi dari satu kegiatan ke kegiatan lain ketika pembelajaran. Tujuan dari penelitian ini adalah untuk mengetahui strategi apa yang digunakan oleh guru dan respon siswa terhadap strategi tersebut. Ketika masa transisi dari satu kegiatan ke kegiatan lainnya selama masa pembelajaran, masalah perilaku siswa kerap muncul dan berpotensi menghabiskan waktu pembelajaran dan juga menghabiskan energi guru. Karena siswa tidak dapat melakukan proses pembelajaran tanpa memperhatukan instruksi dari guru, maka perhatian dari siswa amatlah penting. Penelitian ini dilakukan secara qualitatif dengan cara studi kasus. Data dikumpulkan melalui lima observasi dan dua wawancara. Penelitian ini melibatkan seorang guru Bahasa Inggris dan sebuah kelas tiga sebuah Sekolah Dasar di Bandung. Penelitian ini menunjukan bahwa, guru menggunakan desisting, chant, sound, clapping and singing a song untuk manarik kembali perhatian siswa. Siswa merespon strategi guru dengan dua cara. Cara pertama yaitu, secara postif yang berarti siswa diam dan memperhatikan guru dan respon yang kedua yaitu secara negative yang berarti siswa tidak memperhatikan. Dapat disimpulkan bahwa, Guru dapat menggunakan cara apapun untuk mendapatkan perhatian dari siswa asalkan guru memperhatikan factor-faktor pendukungnya.